2004
DOI: 10.1007/s00239-004-2625-8
|View full text |Cite
|
Sign up to set email alerts
|

Teleost Fish Genomes Contain a Diverse Array of L1 RetrotransposonLineages That Exhibit a Low Copy Number and High Rate of Turnover

Abstract: Retrotransposable elements exhibit a wide range of variation in population dynamics, abundance, and lineage diversity among host genomes across taxa. This range of diversity is illustrated by a single well-defined constituent monophyletic clade of L1 non-LTR retrotransposons that is shared between mammalian and teleost fish genomes. Despite the clear phylogenetic relationships that exist between mammalian and teleost L1 sequences, these elements exhibit markedly different dynamics within their respective taxa.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…Five clades show signs of very recent activity, and two of these clades, L1 and L2, contain numerous simultaneously active families. This situation is similar to that in fish [Volff et al, 2003;Duvernell et al, 2004]. The scarcity of divergent elements and the abundance of very young inserts indicate that the vast majority of retroposons do not reach fixation in the Anolis genome, suggesting a rapid turnover of elements [Novick et al, 2009].…”
Section: Activity Of Tes In Reptilian Genomessupporting
confidence: 55%
“…Five clades show signs of very recent activity, and two of these clades, L1 and L2, contain numerous simultaneously active families. This situation is similar to that in fish [Volff et al, 2003;Duvernell et al, 2004]. The scarcity of divergent elements and the abundance of very young inserts indicate that the vast majority of retroposons do not reach fixation in the Anolis genome, suggesting a rapid turnover of elements [Novick et al, 2009].…”
Section: Activity Of Tes In Reptilian Genomessupporting
confidence: 55%
“…Although TE family numbers are lower in mammals than in fish species, TE copy numbers are generally much higher in mammals than in fishes (Volff 2005). Therefore, TEs in fish genomes appear to have undergone a higher turnover than in the mammalian genomes (Duvernell et al 2004), which is similar to that observed in Drosophila (Eickbush and Furano 2002) . …”
Section: Introductionsupporting
confidence: 58%
“…26 For instance, in Anolis the L1 clade is represented by 20 active families, the origins of which predate the split between reptiles and mammals. Each L1 family is represented by a small number (<100) of very similar copies, reminiscent of the diversity reported in the zebrafish genome 21,28 but drastically more diverse than in modern mammals. 29 A recent study of the newly discovered Ingi clade of non-LTR retrotransposons found these elements in the Anolis genome, suggesting there may be more of these kinds of TEs to be discovered in this genome.…”
Section: Introductionmentioning
confidence: 97%
“…At the other end of the spectrum, some teleostean fish genomes are considerably smaller than mammalian genomes yet contain a comparatively more diverse TE profile, comprised of families usually represented by small numbers (<100) of very similar copies. [20][21][22] is the fact that the majority of these families have recently been active or is still active. Thus the anole genome is exposed to a tremendous level of TE activity, unparalleled among extant amniotes and possibly among vertebrates.…”
Section: Introductionmentioning
confidence: 99%